Peningkatan Semangat Belajar Anak melalui Pendekatan Holistik di Desa Cibuni, Kecamatan Rancabali - Halawa, Nathan; Halawa, Mastriani; Greis, Greis; Salean, Masron Yepsi (Journal Of Human And Education (JAHE), 2024)
Children's learning motivation is an important aspect in the educational process that can influence the achievement of learning indicators. This article discusses the importance of learning motivation in the context of a holistic approach to children's education, especially in Cibuni Village, Rancabali District, Bandung Regency, West Java. Through Community Service activities (PKM), observations, field surveys and literature studies are carried out to identify problems and design appropriate strategies. PKM implementation methods include visits, discussions, education and retreats, with a focus on increasing children's enthusiasm for learning. The results and discussions highlight that holistic education pays attention to all aspects of children's development, with an approach that emphasizes freedom, creativity and balanced growth. Through appropriate teaching strategies, such as immersion, demonstration, involvement, and positive feedback, the PKM implementation team plays a role in providing examples, facilitating, and helping children increase their enthusiasm for learning.